2021
DOI: 10.3390/jpm11101029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Peritumoral Adipose Tissue PET/CT Imaging Features for Predicting Axillary Lymph Node Metastasis in Patients with Breast Cancer

Abstract: We investigated whether textural parameters of peritumoral breast adipose tissue (AT) based on F-18 fluorodeoxyglucose (FDG) PET/CT could predict axillary lymph node metastasis in patients with breast cancer. A total of 326 breast cancer patients with preoperative FDG PET/CT were retrospectively enrolled. PET/CT images were visually assessed and the maximum FDG uptake of axillary lymph nodes (LN SUVmax) was measured. From peritumoral breast AT, 38 textural features of PET imaging were extracted. The diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…In addition to detecting malignant lesions, since [ 18 F]FDG PET/CT can be used to evaluate glucose metabolism in an organ, several studies have demonstrated the clinical use of [ 18 F]FDG PET/CT in estimating the host response to cancers [ 15 , 16 ]. In previous studies, PET imaging parameters of AT were significantly associated with the presence of lymph node metastases and clinical outcomes in diverse cancers, suggesting that PET imaging parameters of AT could be used as surrogate markers of inflammatory response in AT [ 16 , 17 , 18 ]. Since gastric cancer cells also have a substantial interrelationship with peritumoral AT, [ 18 F]FDG PET imaging features of peritumoral AT could reflect this interaction and have a significant association with cancer progression in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to detecting malignant lesions, since [ 18 F]FDG PET/CT can be used to evaluate glucose metabolism in an organ, several studies have demonstrated the clinical use of [ 18 F]FDG PET/CT in estimating the host response to cancers [ 15 , 16 ]. In previous studies, PET imaging parameters of AT were significantly associated with the presence of lymph node metastases and clinical outcomes in diverse cancers, suggesting that PET imaging parameters of AT could be used as surrogate markers of inflammatory response in AT [ 16 , 17 , 18 ]. Since gastric cancer cells also have a substantial interrelationship with peritumoral AT, [ 18 F]FDG PET imaging features of peritumoral AT could reflect this interaction and have a significant association with cancer progression in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, radiomic analysis, which extracts a large number of quantitative features from diagnostic imaging examinations through imaging processing methods, such as textural analysis, has been shown to provide deep and valuable insights into malignant diseases [ 19 ]. In previous studies with malignant diseases, first-order features based on standard uptake value (SUV) histograms, which measured diverse parameters related with SUV distribution, and second-order grey-level co-occurrence matrix (GLCM) features, which showed the SUV intensity level distribution in a neighborhood, have been generally used as radiomic features of PET images [ 17 , 20 ]. These first-order and second-order features have demonstrated superior values in detecting metastasis and predicting prognosis than conventional [ 18 F]FDG PET/CT parameters such as the maximum SUV [ 17 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We screened 32 publications on breast cancer [ 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 ], all employing 18F-FDG. The average number of enrolled patients was 126.8 (range 35–435), 18/32 (56.3%) studies including more than 100 patients; 3 studies (9.3%) were based on prospectively acquired data and 6/32 used an internal independent validation cohort (18.8%).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, GLCM contrast and dissimilarity measure local variations, and GLCM entropy measures the randomness of the SUV distribution of voxel pairs in an image. High values of these features represent a heterogeneous SUV distribution in the image, indicating increased metabolic heterogeneity [ 32 , 33 ]. On the other hand, the GLCM correlation indicates how the SUV of one voxel correlates well with the SUV of its neighborhood voxels over the whole image, which reflects different aspects of voxel intensity distribution from other GLCM features [ 32 ].…”
Section: Discussionmentioning
confidence: 99%